MINT-Bildung im Primarbereich - Qualität im Unterricht zu MINT-Themen stärken - Stiftung Haus der kleinen Forscher (Wissenschaftliche Untersuchungen zur Arbeit der Stiftung "Haus der kleinen Forscher", 2023)
The sixteenth volume of the publication series of the "Haus der kleinen Forscher" Foundation, with a foreword by Andreas Hartinger, presents three contributions that were written as part of the PRIMA!2023 project to provide a professional foundation for the Foundation's work in the primary sector. The content focuses on the one hand on the quality of STEM lessons and on the other hand on the question of how teachers should be trained in order to be able to plan and implement good STEM lessons.